Air-side heat transfer enhancement in fin-tube heat exchangers using forced vibrations under various conditions. (May 2023) - Kim, Minjoong; Han, Changho; Baek, Changhyeon; Kim, Yongchan
Abstract: Forced vibrations can occur in fin-tube heat exchangers (FTHEs) by compressors, fans, and the driving conditions of automobiles. Accordingly, the effects of forced vibrations on the heat transfer performance of FTHEs in refrigeration systems and heat pumps should be investigated in detail for their practical design. However, few studies have investigated the improvement in heat transfer by vibrations in FTHEs. In this study, air-side heat transfer enhancement in FTHEs by applying forced vibrations is experimentally investigated. The heat transfer performance of the FTHEs was measured by varying the air-side Reynolds number, vibrational frequency, vibrational amplitude, and fin pitch. For practical purposes, the heat transfer characteristics of the FTHEs were analyzed under constant vibrational power, force, and velocity. The heat transfer enhancement increased with an increase in the vibrational frequency, amplitude, and fin pitch, whereas it decreased with an increase in the air-side Reynolds number. A correlation for heat transfer enhancement using forced vibrations was developed as a function of nondimensional operating and geometrical parameters. The results can be used to predict heat transfer enhancement by vibrations and the FTHE design for heating, ventilating, and air-conditioning systems. Highlights: Heat transfer improvement of fin-tube heat exchangers using vibrations is studied. Vibrational amplitude, frequency, and fin pitch effects are measured and analyzed. Vibrational velocity and boundary layer show substantially impact enhancement. Empirical correlation for heat transfer enhancement using vibrations is developed.